"Settling for less": Designing undergraduate nursing curricula in the context of national accreditation. Issue 2 (April 2017) - Ralph, Nicholas; Birks, Melanie; Cross, Wendy; Chapman, Ysanne
Summary: The quality of undergraduate nursing education is essential to producing graduates that are safe and effective practitioners, relevant to the broader contexts of care. National accreditation standards are focused on ensuring the quality of nursing programs in terms of public interest and safety. To ensure that nursing programs achieve the outcomes expected of them, effectively designing curricula as part of an accredited program is central to quality assurance in nursing education. The aim of the study is to explore the process of curriculum design in the context of national accreditation processes. A qualitative grounded theory methodology was adopted with interviews and document analysis undertaken. Findings revealed significant issues with the approaches used to inform curriculum design, resourcing, and staff capacity in the context of undergraduate nursing education. Strong whole-of-course curriculum design processes form the foundation of a quality system of undergraduate nursing education. The deficiencies in current practice have significant implications for the future of the nursing profession. While no clear and immediate solution is evident, identifying the nature of such limitations and implementing systematic, evidence-informed approaches to the process is crucial to improving the quality of undergraduate nursing education.